Principles of auditing - Meigs, Walter B.; Whittington, Ray; Meigs, Robert F. (Homewood, Ill. : R.D. Irwin, 1985)
The book examines auditing techniques and reorganized the text to enable students and users understand the philosophy and environment of auditing.
Includes index.
Includes bibliographies
ucj 17/01/2019
Loans
Keywords: Auditing